2020
DOI: 10.1177/1534734620930120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Empowerment on HbA1c Levels and Healing of Diabetic Foot Ulcers

Abstract: Objective. To evaluate the effectiveness of family empowerment through educational interventions against HbA1c level and healing progress of diabetic foot ulcers. Method. A quasi-experimental design was employed involving 33 participants from 4 wound care clinics in Makassar, eastern Indonesia. The intervention group consisted of 17 participants and their families; the control group was composed of 16 participants who received nonstructural education. Family empowerment was measured by the Indonesian version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 24 publications
0
28
0
2
Order By: Relevance
“…The review included 10 studies. Three of the studies came from the USA [ 39 41 ], two from China [ 42 , 43 ], two from Indonesia [ 44 , 45 ] and one each from Iran [ 46 ], Ireland [ 47 ], and India [ 48 ]. The total number of participants with diabetes was 5532.…”
Section: Results Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The review included 10 studies. Three of the studies came from the USA [ 39 41 ], two from China [ 42 , 43 ], two from Indonesia [ 44 , 45 ] and one each from Iran [ 46 ], Ireland [ 47 ], and India [ 48 ]. The total number of participants with diabetes was 5532.…”
Section: Results Of Reviewmentioning
confidence: 99%
“…The total number of participants with diabetes was 5532. Only five studies [ 39 , 41 , 43 45 ] reported the characteristics and number of caregivers involved which was 359. Majority of caregivers were female (73.6%), and family relationship was mostly spouse or partner (53.6%), son/daughter (28.3%), or other family members (14.7%).…”
Section: Results Of Reviewmentioning
confidence: 99%
“…Setiap pertemuan diawali dengan mereview hasil pelatihan sebelumnya, dan untuk mempermudah pemahaman pasien Hipertensi, maka diberikan pula link untuk et al, 2019), meningkatkan pengetahuan dan sikap anggota keluarga dalam membantu proses penyembukan luka kaki diabetes pada anggota keluarganya yang menderita DM (Appil et al, 2020), meningkatnya pemahaman perangkat Desa Mranggen setelah diberikan pelatihan Komputer Microsoft Office Exel (Niati, Soelistiyono and Ariefiantoro, 2019).…”
Section: B Pelaksanaan Dan Metodeunclassified
“…Many educative-supportive programs have been conducted for patients with chronic diseases, such as DM, to determine the regularity of their diet and treatment. 28,31 In patients with Tuberculosis, a study has also been conducted and proven using educative-supportive programs to achieve more optimal healing. 32 Therefore, the researcher aims to assess the effectiveness of supportive-educative ROM exercises on health outcomes in patients with stroke in home care settings because the healing process of patients with stroke requires a special approach to achieve maximum outcomes compared with health education in general, so a method of guidance or assistance and learning support for patients is needed, in the form of an educative-supportive approach to change patients’ behavior, to be independent and optimal in their care through the teaching, guiding, and supporting stages.…”
Section: Introductionmentioning
confidence: 99%